Comparisons of vortical flow and cavitation inside a Francis turbine with different draft tubes. Issue 1 (June 2021) - Geng, Chen; Zhang, Ruizhi; Tsujimoto, Yoshinobu; Nishi, Michihiro; Luo, Xianwu
Abstract: It is well known that strong pressure fluctuation will occur in the draft tube of a Francis turbine operated under part-load operation. The pressure fluctuation is usually due to the vortex rope as well as cavitation. However, the vortical flow and pressure field are dependent on the geometry of draft tube of Francis turbine. In this study, hydraulic performance and pressure fluctuation have been tested for a model Francis turbine. The internal flow for the turbine is investigated numerically. It is confirmed that the numerical results predict reasonably the hydraulic performance and the pressure fluctuation due to vortex rope at part-load operation. For a better understanding of the vortical flow in the model turbine, a conical draft tube is used instead of the conventional elbow draft tube. The vorticity transport equation is applied to analyze the vortex evolution inside Francis turbine based on the unsteady flow simulation. The flow mechanism of the vortex rope and pressure fluctuation with different draft tubes is discussed. It is shown that both cavitation and the bending structure influence the vortex rope, which will cause a significant difference in the distribution of pressure fluctuation.